GAMBARAN PERILAKU SOPAN SANTUN PADA ANAK USIA 5-6 TAHUN DI RA RABBANI KECAMATAN TANETE RIATTANG KABUPATEN BONE - Detsy Hatmala Citra; Mahmud, Bonita; Sitti Fatimah (Institut Agama Islam Negeri Bone, 2025)
This thesis investigates the role of teachers in instilling polite behavior among children aged 5–6 years at RA Rabbani, Tanete Riattang District, Bone Regency. The study aims to examine how teachers foster polite behavior and to identify the forms of polite behavior demonstrated by children in early childhood education. A descriptive qualitative research design was employed, drawing on pedagogical and psychological perspectives. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate three main forms of polite behavior among children aged 5–6 years: (a) mutual respect, reflected in caring attitudes toward others without undermining one’s own self-esteem; (b) expressing gratitude as a way of appreciating the time and effort of others; and (c) socialization as a process that supports the internalization of values in the development of children’s attitudes and personality.